Changes of Land Use and Land Cover with the Diversity of Fishes, Aquatic Plants, and Bird’s Species at Wetland Ecosystem - Mohammad Zahangeer Alam; Md. Abdullahil Baki Bhuiyan; Hasan Muhammad Abdullah; Suma Rani Ghosh; Mohammad Maksudul Hassan; Ruzina Akter; M. Rokonuzzaman; Mohammad Shah Alam (The Scientific World Journal)
Bangladesh is rich in wetland biodiversity with aquatic plants, fishes, and birds. Mohanganj Upazila is known as the capital of lower Bangladesh. The present study focuses on the changes of land use and land cover (LULC) with a diversity of species that are being least concerned (LC), vulnerable (VU), and endangered (EN). Over the last two decades, the wetland species of Mohanganj were gradually declined. Our results showed that 19 fish, 4 aquatic plants, and 7 bird species were LC in 2015. Among the fish and aquatic plant species, 6 fish species (Wallago attu, Ompok pabda, Channa punctate, Chitala chitala, Salmostoma phulo, and Corica soborna) and 2 aquatic plant species (Nymphaea nouchali and Nymphaea lotus) were VU during the dry and rainy season of 2017 and 2019, respectively. In the dry season of 2019, 4 fish species (W. attu, O. pabda, C. punctate, and Ch. chitala), 2 aquatic plant species (N. nouchali and N. lotus), and 7 bird species (Anas platyrhynchos, Ardeola grayii, Gyps bengalensis, Alcedo atthis, Phalacrocorax fuscicollis, Porphyrio porphyria, and Larus ridibundus) were EN. Among the species, W. attu, N. nouchaii, G. bengalensis, P. porphyria, and L. ridibundus were extremely endangered categories. Changes in LULC, the establishment of settlements for the increasing population, indiscriminate use of pesticides, environmental pollutions, and climate change are the potential reasons for declining trends of wetland biodiversity. Stern actions on land use policy, expansion of organic agriculture, bioremediation of industrial effluents, and adoption of sustainable environmental policies should be taken by the Government of Bangladesh for immediate conservation of wetland biodiversity.